2009
DOI: 10.5551/jat.no1271
|View full text |Cite
|
Sign up to set email alerts
|

A Promoter Polymorphism of Lamin A/C Gene is an Independent Genetic Predisposition to Arterial Stiffness in a Japanese General Population (The Tanno and Sobetsu Study)

Abstract: Aim:We examined the hypothesis that there is a positive, independent association between polymorphisms of lamin A/C gene (LMNA) and arterial stiffness in Japanese. Methods: The subjects were 261 men (mean age, 64.4 0.7 years) selected from inhabitants of the towns of Tanno and Sobetsu in a rural area of Japan who underwent medical check-ups. We conducted clinical examinations, including measurement of bilateral brachial-ankle pulse wave velocity (baPWV) as a marker of arterial stiffness, and genetic analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The significant association of genetic ancestry with arterial elasticity in this study is supported by several studies and reviews of genetic variants associated with measures of vascular dysfunction(3250), including variants in the angiotensinogen, beta-adrenergic receptor, and advanced glycation endproducts receptor genes, as well as several genes involved in cardiac function and structure; however, these studies were in participants of European descent. Our study suggests that there is genetic heterogeneity among both Hispanics and African-Americans, and that this heterogeneity is important in determining measures of vascular dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…The significant association of genetic ancestry with arterial elasticity in this study is supported by several studies and reviews of genetic variants associated with measures of vascular dysfunction(3250), including variants in the angiotensinogen, beta-adrenergic receptor, and advanced glycation endproducts receptor genes, as well as several genes involved in cardiac function and structure; however, these studies were in participants of European descent. Our study suggests that there is genetic heterogeneity among both Hispanics and African-Americans, and that this heterogeneity is important in determining measures of vascular dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…A mutant of the LMNA gene has been reported to be associated with a blunted vasodilator response and elevated SBP/DBP levels. 56,57 cg11376147 is in the enhancer region of SLC43A1 , and although the impact of enhancer DNA methylation on gene expression is complex, previous literature has indicated that methylation of enhancer elements influences tissue-specific gene expression. 58 SLC43A1 is related to metabolic phenotypes, particularly lipids and adiposity, which may synergistically affect the pathogenesis of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…64, 65 This relatively frequently studied gene has been linked to several cancers including non-small-cell lung and colorectal, 66, 67 as well as cardiovascular pathophysiology. 68 LAMA1 has also been associated with pharmacogenetic moderation of thiazolidinedione-induced side effects to diabetes treatment and, 69 more relevantly, with moderating the effects of antidepressant buproprion on smoking cessation. 70 Thus, robust GWAS support and prior evidence of antidepressant moderation suggest LAMA1 as a plausible candidate for future pharmacogenetic and functional analyses.…”
Section: Discussionmentioning
confidence: 99%